2006
DOI: 10.1080/10826080600847894
|View full text |Cite
|
Sign up to set email alerts
|

Club Drugs as Causal Risk Factors for HIV Acquisition Among Men Who Have Sex with Men: A Review

Abstract: We reviewed medical and psychology databases for articles published between January 1980 and August 2005 demonstrating associations between HIV/Sexually Transmitted Infection risk and club drug use. Seventy-four articles were reviewed, of which 30 provided adjusted risk ratios for associations between HIV/sexually transmitted infection risk and club drug use among men who have sex with men. Definitions and lists of club drugs were broad and inconsistent. We constructed a conceptual framework of biologically pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
185
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(200 citation statements)
references
References 198 publications
(232 reference statements)
12
185
3
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12][13][14][15] Two recent and substantive literature reviews describe how assessment of substance use with or without sex among MSM has been inconsistent among prior studies. 16,17 Despite these inconsistencies, several key themes were noted. Vosburgh and colleagues indicated that event-level use of methamphetamine and binge alcohol use provided the strongest causal link for acquisition of HIV among MSM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10][11][12][13][14][15] Two recent and substantive literature reviews describe how assessment of substance use with or without sex among MSM has been inconsistent among prior studies. 16,17 Despite these inconsistencies, several key themes were noted. Vosburgh and colleagues indicated that event-level use of methamphetamine and binge alcohol use provided the strongest causal link for acquisition of HIV among MSM.…”
Section: Introductionmentioning
confidence: 99%
“…16 Along with methamphetamine use with sex, Drumright and colleagues also found evidence for a causal link of MSM's use of volatile nitrates with sex and increased risk for HIV acquisition. 17 In addition to the association between the use of substances with sex and HIV acquisition among MSM, the use of stimulant-type drugs, such as methamphetamine, cocaine, crack, amphetamine, and ecstasy, also appears to impair their adherence to antiretroviral treatment (ART) for HIV more than the use of other types of drugs. 18,19 Studies have also documented characteristics of MSM who use illegal (e.g., methamphetamines) and prescription drugs (e.g., erectile dysfunction medications (EDM)) with sex as gay, white, and/or 40 years of age and older.…”
Section: Introductionmentioning
confidence: 99%
“…The research has been beset by problems in consistency of terminology, differences in the drugs examined, poor adjustment for confounding variables, and a reliance on cross-sectional research (Drumright, Patterson et al 2006). This problem makes it difficult to tease apart the possible explanations for a complex and multilayered problem.…”
Section: Introductionmentioning
confidence: 99%
“…79 Whatever the relation between recreational drug use and risk-taking (and the relation is certainly multiple), numerous studies have found that infection with HIV and other sexually transmissible infections (STIs) and blood-borne viruses (BBVs) is more likely to occur among gay and MSM who consume recreational drugs than those who do not. [80][81][82] Reasons for this extend beyond straightforward explanations that attribute individual sexual risk-taking to substance use 69 to include a range of contextual factors and cultural variables. For example, the sexual networks of men who use drugs for gay sex are characterised by a higher prevalence of HIV-positive participants and lower rates of condom use (often as a result of attempted serosorting).…”
Section: Sexualised Drug Usementioning
confidence: 99%